Developmental venous anomaly associated ischemic stroke caused by minor head trauma: A case report. Issue 38 (18th September 2020) - Lee, Chan-Hyuk; Shin, Byoung-Soo; Kang, Hyun Goo
Abstract: Rationale: A developmental venous anomaly (DVA) is the most common intracranial congenital anomaly and is mostly asymptomatic. Thrombosis rarely develops in a DVA due to hypercoagulation. We report a case of ischemic stroke in the area of a DVA after minor head trauma in a patient with DVA and without a predisposition thrombosis. Patient concerns: A healthy 17-year-old male was admitted to the emergency room due to left hemiparesis, which was caused by a ball hitting the right side of his head during a soccer game. Diagnosis: Brain magnetic resonance (MR) susceptibility-weighted image showed several small veins draining to the central vein in the area from the right posterior putamen to the periventricular white matter. Interventions: We diagnosed the patient with an ischemic stroke associated with a DVA and administered antiplatelet agents. The patient's autoantibodies (including antiphospholipid antibody) and factors of blood coagulation were normal. Outcomes: The left hemiparesis of the patient worsened by the second day of admission. Moreover, high signal intensity was observed in the DVA region of the diffusion weighted image of brain MR. The patient's symptoms gradually improved afterward, and left hemiparesis recovered fully 3 weeks after the onset. Lessons: DVAs may predispose to ischemic stroke due to thrombosis and hypercoagulation, although it is rare. It is necessary to consider the possibility of ischemic stroke due to minor head trauma, even without factors causing hypercoagulation.